The Meaning of Balance of Payments Statistics in an Interdependent World - Bame, Jack (IMF Working Papers; Working Paper, 1994)
The relevance of the standard measures of international transactions in goods and services as reflected in the fifth edition of the IMF Balance of Payments Manual (BPM) and in the 1993 System of National Accounts (SNA) has been questioned in several recent studies and articles. Alternative measures have been proposed, that either (i) substitute an ownership basis for transactions for the long-established residency basis; (ii) maintain the residency basis but combine net direct, investment income with goods and services; or question the validity of any measures in the form of net balances as a guide to policy. This paper affirms the central role of residency in the international accounts, discusses the supplementary value of alternative proposals, and notes the importance of international efforts to improve and refine the measurement of external transactions based on the principles of the BPM and SNA.